2004
DOI: 10.1177/1049732304267753
|View full text |Cite
|
Sign up to set email alerts
|

Struggling with Recovery: Participant Perspectives on Battling an Eating Disorder

Abstract: Recovery from an eating disorder encompasses a complex matrix of mental, physical, and social factors. Although methodological differences affect rates of reported recovery (from 24 to 76%), many women are not experiencing full recoveries from eating disorders. This trend is apparent in persons who discontinue severely destructive behaviors but continue to exhibit psychiatric problems and impairment in social and occupational roles. The purpose of this grounded theory study was to provide an explanatory schema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 25 publications
3
60
0
Order By: Relevance
“…In addition, previous qualitative studies draw attention to recovery being a relational process that occurs in the context of close and supportive relationships [1][2][3][4][5] Some authors found that treatment did not facilitate recovery [2][3] , which indicates that processes outside therapy play an important part in recovery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous qualitative studies draw attention to recovery being a relational process that occurs in the context of close and supportive relationships [1][2][3][4][5] Some authors found that treatment did not facilitate recovery [2][3] , which indicates that processes outside therapy play an important part in recovery.…”
mentioning
confidence: 99%
“…Previous research into recovering from AN has predominantly focused on defining the recovery from AN the patient perspective [1][2][3][4][5][6] and looked at predictors of recovery using quantitative criteria such as length of treatment and follow up or age at onset [7][8][9] with mixed results.…”
mentioning
confidence: 99%
“…19,24 Spirituality is seen as a major condition to confront the disease in some studies. The exercise of spirituality, independent of religion, brings a feeling of hope and value to life and helps the patient to better understand his condition.…”
Section: Recoverymentioning
confidence: 99%
“…13-15,23, 24 In eating disorders, body control seems to be the control of life itself. The scale is a concrete way of checking this control.…”
Section: Negative Feelingsmentioning
confidence: 99%
“…"Finding me" as detached from "the eating disordered me" is a psychological and existential feature of recovery (Björk & Ahlström, 2008;Weaver et al, 2005) representing a change of focus from fat, appearance and the counting of calories to a search for meaning and purpose in life (D'Abundo & Chally, 2004;Matusek & Knudson, 2009). Many women describe recovery as being more than just an individual with a preoccupation with food calories and appearance (Lamoureux & Bottorff, 2005) or being preoccupied with the planning of binges and developing plans to conceal them (Pettersen et al, 2008).…”
Section: Changes In Self-image and Experiences Of Identitymentioning
confidence: 99%